2008
DOI: 10.1016/j.ijsolstr.2007.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical analysis of sheet metal instability using a stress based criterion

Abstract: Strain based Keeler-Goodwin diagrams are widely used in forming processes to predict onset of local necking. Plastic instability is determined once the forming limit strain is exceeded. Use of these diagrams requires proportional strain paths, which is not necessarily the case in sheet metal forming operations. In many forming processes, the strain path changes during deformation. This may change the forming limit curve significantly. In the paper, a stress based forming limit criterion is adopted to deal with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 17 publications
0
60
0
1
Order By: Relevance
“…However, there is still a need to continuously study, improve and validate the influence of many parameters in the numerical simulations and models due to ever-increasing demands for more accurate predictions of, for example, material failure or for mimicking the responses recorded in tests that have been carried out (see, for example, Ehlers et al 2008). Often, both the accuracy and reliability of numerical models and what they aim to represent are discussed, together with whether or not their applicability is general or limited to specific conditions or types of analyses (see Alsos et al 2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is still a need to continuously study, improve and validate the influence of many parameters in the numerical simulations and models due to ever-increasing demands for more accurate predictions of, for example, material failure or for mimicking the responses recorded in tests that have been carried out (see, for example, Ehlers et al 2008). Often, both the accuracy and reliability of numerical models and what they aim to represent are discussed, together with whether or not their applicability is general or limited to specific conditions or types of analyses (see Alsos et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…It is to be noted that, even though the evaluation procedure is designed to reduce the scatter, there is larger scatter in results from the measurements for fracture in the ε 1 direction in contrast to the ε 2 direction ). Alsos et al (2008) proposed a criterion for the onset of instability (necking) in sheet metal, which is referred to as the Bressan-Williams-Hill (BWH) criterion. It searches for local instability and applies only to membrane stresses and strains, i.e.…”
Section: Fld Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forming limit tests were conducted to study the multiaxial failure behaviour of the material in terms of necking and fracture. The failure criteria that were verified against the tests were chosen among those available in the FE software Abaqus and the Bressan-Williams-Hill (BWH) criterion proposed by Alsos et al 2008. The experimental and numerical results from the tensile tests confirmed that Barba's relation is valid for handling stress-strain dependence on the length scale used for strain evaluation after necking.…”
Section: Introductionmentioning
confidence: 98%
“…However, there is still a need to continuously study, improve and validate the influence of many parameters in the numerical simulations and models due to ever increasing demands for more accurate predictions of, for example, material failure or for mimicking the responses recorded in tests that have been carried out. Often, both the accuracy and reliability of numerical models and what they aim to represent are discussed, together with whether or not their applicability is general or limited to specific conditions or types of analyses, see Alsos et al [1].…”
Section: Introductionmentioning
confidence: 99%